Observations on Oceanography and Sedimentation at Pangnirtung Fiord, Baffin Island - Gilbert, R. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1978)
Pangnirtung Fiord is a glacial trough draining the southwest portion of Penny Icecap, Baffin Island. Sills associated with riegels divide the fiord into four basins. Despite a large inflow of sediment from streams draining the glaciers and Penny Icecap, glacio-marine sediments have been deposited in sufficient thickness to mask glacial features only in the central portion of the fiord. A major trench in the fiord floor is believed to result from erosion by turbidity currents. A shallow sill (12 to 22 m below mean tide level) at the mouth of the fiord, a large tidal range (up to 6.7 m), and moderate fresh water inflow strongly influence circulation and stability of fiord water. Replacement of bottom water occurs frequently or continuously during the year and helps to determine the distribution of sediment. The oxygen~rich bottom water supports a large benthia fauna which severley bioturbates the sediments making them useless for the interpretation of Holocene events in the region.